Asymptomatic Liver Abscesses Mimicking Metastases in Patients after Whipple Surgery: Infectious Complications following Percutaneous Biopsy—A Report of Two Cases. (3rd September 2012) - Zhang, Kan K.; Mayody, Majid; Shah, Rajesh P.; Vakiani, Efsevia; Getrajdman, George I.; Brody, Lynn A.; Solomon, Stephen B.
Abstract : We present two cases of hepatic abscesses that mimicked metastases in patients having undergone Whipple surgery. Both patients had similar imaging features on computed tomographic (CT) scan and ultrasound, and at the time of referral for biopsy neither patient was clinically suspected to have liver abscess. Both patients underwent biopsy of liver lesions and developed postprocedural infectious complications.